Beetroot juice does not enhance altitude running performance in well-trained athletes - Arnold, J. T.; Oliver, S. J.; Lewis-Jones, T. M.; Wylie, L. J.; Macdonald, J. H. (Applied Physiology, Nutrition, and Metabolism, 2015)
We hypothesized that acute dietary nitrate (NO3-) provided as concentrated beetroot juice supplement would improve endurance running performance of well-trained runners in normobaric hypoxia. Ten male runners (mean (SD): sea level maximal oxygen uptake, 66 (7) mL/kg/min; 10 km personal best, 36 (2) min) completed incremental exercise to exhaustion at 4000 m and a 10-km treadmill time-trial at 2500 m simulated altitude on separate days after supplementation with ~7 mmol NO3- and a placebo at 2.5 h before exercise. Oxygen cost, arterial oxygen saturation, heart rate, and ratings of perceived exertion (RPE) were determined during the incremental exercise test. Differences between treatments were determined using means [95% confidence intervals], paired sample t tests, and a probability of individual response analysis. NO3- supplementation increased plasma nitrite concentration (NO3-, 473 (226) nmol/L vs. placebo, 61 (37) nmol/L, P < 0.001) but did not alter time to exhaustion during the incremental test (NO3-, 402 (80) s vs. placebo 393 (62) s, P = 0.5) or time to complete the 10-km time-trial (NO3-, 2862 (233) s vs. placebo, 2874 (265) s, P = 0.6). Further, no practically meaningful beneficial effect on time-trial performance was observed as the 11 [-60 to 38] s improvement was less than the a priori determined minimum important difference (51 s), and only 3 runners experienced a "likely, probable" performance improvement. NO3- also did not alter oxygen cost, arterial oxygen saturation, heart rate, or RPE. Acute dietary NO3- supplementation did not consistently enhance running performance of well-trained athletes in normobaric hypoxia.